Prospective cohort study of water immersion for labour and birth compared with standard care in an Irish maternity setting - Barry, Paula L (BMJ Open, 2020)
OBJECTIVE: To examine the birth outcomes for women and babies following water immersion for labour only, or for labour and birth. DESIGN: Prospective cohort study. SETTING: Maternity hospital, Ireland, 2016–2019. PARTICIPANTS: A cohort of 190 low-risk women who used water immersion; 100 gave birth in water and 90 laboured only in water. A control group of 190 low-risk women who received standard care. METHODS: Logistic regression analyses examined associations between water immersion and birth outcomes adjusting for confounders. A validated Childbirth Experience Questionnaire was completed. MAIN OUTCOME MEASURES: Perineal tears, obstetric anal sphincter injuries (OASI), postpartum haemorrhage (PPH), neonatal unit admissions (NNU), breastfeeding and birth experiences. RESULTS: Compared with standard care, women who chose water immersion had no significant difference in perineal tears (71.4% vs 71.4%, adj OR 0.83; 95% CI 0.49 to 1.39) or in OASI (3.3% vs 3.8%, adj OR 0.91; 0.26–2.97). Women who chose water immersion were more likely to have a PPH ≥500 mL (10.5% vs 3.7%, adj OR 2.60; 95% CI 1.03 to 6.57), and to exclusively breastfeed at discharge (71.1% vs 45.8%, adj OR 2.59; 95% CI 1.66 to 4.05). There was no significant difference in NNU admissions (3.7% vs 3.2%, adj OR 1.06; 95% CI 0.33 to 3.42). Women who gave birth in water were no more likely than women who used water for labour only to require perineal suturing (64% vs 80.5%, adj OR 0.63; 95% CI 0.30 to 1.33), to experience OASI (3.0% vs 3.7%, adj OR 1.41; 95% CI 0.23 to 8.79) or PPH (8.0% vs 13.3%, adj OR 0.73; 95% CI 0.26 to 2.09). Women using water immersion reported more positive memories than women receiving standard care (p<0.01). CONCLUSIONS: Women choosing water immersion for labour or birth were no more likely to experience adverse birth outcomes than women receiving standard care and rated their birth experiences more highly.